THE EFFECT KIND OF WRITTEN TEST AND BELIEF OF MATHEMATIC TOWARD MATHEMATICRESULT - Iskandar (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2019)
This study aim is to find out the effect kind of written test and belief of mathematic toward mathematic result. The sample in this research is the second grade of vocational school of YPI Way Jepara. The dependent variable is mathematic result and independent variable is kind of written test that are depent to problem solving test and structure exercise method test, and belief of mathematic that are depent to positive and negative category. The instrument that use are mathematic result test and quisioner about mathematic belief. The method used was an quasi experiment method using the treatment by level design 2 x 2. The research hypotheses were tested using two way analysis of variance (ANAVA). The study concluded that mathematic result which the student have positive belief of mathematic is more effective treat by problem solving test, and the mathematic result of the student that